The complete mitochondrial genome of Hyriopsis cumingii (Unionoida: Unionidae): genome description and related phylogenetic analyses. (3rd May 2016) - Wei, Min; Yang, Shoubao; Yu, Peng; Wan, Quan
Abstract: Hyriopsis cumingii is a freshwater pearl mussel in china, easily identified by a big sail-like bulging at back edge of the mussel. In the present study, we reported the complete mitochondrial genome of H. cumingii . It was 16, 958 bp in length, and it contained 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes. Besides, we conducted alignment with other two different individuals of H. cumingii and phylogenetic analysis with closely related species.